if 5x - 4y =7 and xy = 8, find : 125xcube - 64ycube
Answers
Answered by
7
Solution:
_____________________________________________________________
Given:
=> 5x - 4y = 7,
=> xy = 8,
_____________________________________________________________
To find :
=> 125x³ - 64y³ =?
_____________________________________________________________
if 5x - 4y =7,.
=> (5x - 4y)² = (7)² squaring both the sides
=> (5x)² - 2(5x)(4y) + (4y)² = (7)²
=> 25x² - 40xy + 16y² = 49
=> 25x² -40(8) +16y²= 49
=> 25x²- 320 + 16y² = 49
=> 25x² + 16y² =49 + 320
=> 25x² + 16y² =369,...(i)
_____________________________________________________________
We can change the equation like this too,
=> 125x³ - 64y³
=> (5x)³ - (4y)³
_____________________________________________________________
As, we know the identity that,.
=> a³ - b³ = (a - b)(a² + ab + b²)
let,
=> a = 5x ,
and
=> b = 4y,.
then, use the identity,.
=> (5x)³ - (4y)³ = (5x - 4y) ((5x)² + (5x) (4y) + (4y)²)
=> 125x³ - 64y³ = (7) (25x² +20xy + 16y²)
=> 125x³ - 64y³ = 7 (25x² + 16y² + 20(8))
=> 125x³ - 64y³ = 7 (369 + 160)
=> 125x³ - 64y³ = 7 (529)
=> 125x³ - 64y³ = 3703,..
_____________________________________________________________
Hope it Helps !!
_____________________________________________________________
Given:
=> 5x - 4y = 7,
=> xy = 8,
_____________________________________________________________
To find :
=> 125x³ - 64y³ =?
_____________________________________________________________
if 5x - 4y =7,.
=> (5x - 4y)² = (7)² squaring both the sides
=> (5x)² - 2(5x)(4y) + (4y)² = (7)²
=> 25x² - 40xy + 16y² = 49
=> 25x² -40(8) +16y²= 49
=> 25x²- 320 + 16y² = 49
=> 25x² + 16y² =49 + 320
=> 25x² + 16y² =369,...(i)
_____________________________________________________________
We can change the equation like this too,
=> 125x³ - 64y³
=> (5x)³ - (4y)³
_____________________________________________________________
As, we know the identity that,.
=> a³ - b³ = (a - b)(a² + ab + b²)
let,
=> a = 5x ,
and
=> b = 4y,.
then, use the identity,.
=> (5x)³ - (4y)³ = (5x - 4y) ((5x)² + (5x) (4y) + (4y)²)
=> 125x³ - 64y³ = (7) (25x² +20xy + 16y²)
=> 125x³ - 64y³ = 7 (25x² + 16y² + 20(8))
=> 125x³ - 64y³ = 7 (369 + 160)
=> 125x³ - 64y³ = 7 (529)
=> 125x³ - 64y³ = 3703,..
_____________________________________________________________
Hope it Helps !!
Similar questions